Impedance spectroscopy studies of the chlorophosphate glasses. (2022) - Ouachouo, L.; Bih, L.; Haily, E.; Jerroudi, M.; Saadoune, I.
Abstract: The lithium halide doped phosphate glass system was investigated using LiCl as an additive halide. Glass of composition (1-x) (0.5LiCl–0.5Li2 O)–xP2 O5 with x = 0.65; 0.60; 0.55 and 0.50 were prepared by the melt quench method. Electrical conductivity measurements were made in the temperature range from RT to 383 K using the impedance spectroscopy technique. The frequency dependence as well as the electrical modulus of the glasses are investigated. The results showed that the conduction mechanism in these glasses is governed by the correlated barrier hopping (CBH) mechanism and the conductivity relaxation is of the non-Debye type.